'Accurate History and Facts' or Memoir?: Unravelling the Weave of History and Life Narrative in the Black Hills. Issue 4 (2nd October 2019) - Beard, Laura J.
ABSTRACT: This essay explores how John S. McClintock's Pioneer Days in the Black Hills: Accurate History and Facts Related by One of the Early Day Pioneers, originally published in 1939 and republished by the University of Oklahoma Press in 2000, is employed as a historical source by historians and in popular cultural contexts (including by scriptwriters for the HBO series 'Deadwood'). The essay underscores palpable tensions in a text in which McClintock presents himself as an eyewitness to key moments in Black Hills history, yet claims not to want to speak of himself. Tracing these tensions in the text reveals interesting insights into how we read and classify forms of life narratives and how those life narratives may serve historical understanding and writing. In writing of a life narrative written by an ancestor, I discuss my own relation to the man and the memoir as well the challenges that arise in working on life narratives by kin.